Gynecomastia - a literature review of management, diagnosis and treatment - Szumlas, Zuzanna; Jurek, Aleksander; Mrozek, Łukasz; Klocek, Konrad; Zwolski, Maciej; Puchalski, Krzysztof; Kostecki, Bartosz; Hajduk, Aleksandra (Journal of Education, Health and Sport, 2023)
Introduction and Purpose: Gynecomastia is a common clinical problem that can also be a symptom of many serious disorders. The aim of this study is to analyze the etiology, pathogenesis, diagnostics, as well as pharmacological and surgical treatment, while also addressing the psychological aspect of the condition. State of Knowledge: Gynecomastia is the development of noncancerous breast tissue in males. It can occur unilaterally or bilaterally and may cause pain. It can be a natural occurrence during infancy, adolescence, and and in older age. It is usually accompanied by an imbalance between estrogens and androgens. Hormonal disorders lead to the growth of stromal and ductal proliferation. In the diagnostic process, the most important aspect is establishing the cause of the condition, allowing for the implementation of appropriate treatment. Gynecomastia can cause a decrease in quality of life, depression, anxiety, and reduced self-esteem. Conclusions: Gynecomastia is a complex condition that requires an individualized approach to the patient. It can be a side effect of medication use, result from an underlying disease, or occur idiopathically. Surgical treatment forms the basis of the therapeutic process. Currently, combined surgical techniques are most commonly used to achieve the best cosmetic effect.